Proposed Operation Strategy For A Better Service Capacity and Quality at Urban Laundry and Dry Cleaning, Bandung - Gandwinatan, Jefry; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. Urban Laundry & Dry Cleaning is a company engaged in the field of kilos and item laundry services in Bandung that has two major problems in its operation system, it is the target of completion of orders that are often not achieved and the swapped case between customer's clothes. Based on the analysis of the effective capacity and actual demand that occurred during May 2015 until September 2015, it is found two important points to be the root of existing problems. The first is the company's dependency on interpretation on two important processes in production systems/services, namely the recording process and Checking. Interpretation on Characteristic Writing Method caused interruptions and misunderstanding during the process. The second is the high impact of daily demand fluctuations during the month. Interpretation itself can be eliminated by using Write & Tag Method instead of the old method. Urban L&DC can improve the service capacity of up to 21.0% in Kilos laundry service. To mitigate the effects of fluctuations in demand, companies are encouraged to add new workers by adopt the system of part-time labor. The application of these two steps simultaneously increase the target completion of the order of 28.6% to 94.3% and the rate of service quality of critical condition (94.7%) to the optimum conditions (72.9%). In order to Write & Tag Method be able to run consistently, the company is obliged to make a Standard Operating Procedure (SOP) that is easily understood by the entire workforce. To recruit a part-time labor, Urban L&DC can publish the information through online media, newspaper, or through the recommendation of fellow workers.Ã‚Â Keywords : operation strategy, service quality, capacity, laundry, Write & Tag Method